Performance and Carcass Characteristics of Broilers Under Diets Supplemented with Whole Grains - Sharma, NK; Sapkota, M; Sah, R; Sharma, MP; Creswell, D; Sharma, N (Nepal Journal of Science and Technology, 2013)
This study was conducted at the Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan with the objective to study the effects of mixing starter diet with whole grains on the performance and carcass characteristics of broilers. The control group (T1) was fed only with the commercial starter and grower diets throughout the experimental period. Other treatment groups, T2, T3, and T4 received commercial starter diets supplemented with whole wheat, cracked maize and bajra pearl millet (Pennisetum glaucam) respectively from day 6. At 37 days, cumulative feed intakes (FI) were significantly lower (P<0.01) for all the whole grain treated groups, the lowest FI being noted in T2 followed by T4 and T3. Cumulative body weights at 37 days were considerably poorer in the 3 whole grain treatments. Feed conversion ratio in T3 and T4 were equal to T1, at 1.70 whereas T2 FCR was 13 points higher than T1. Lower carcass yield and breast yield (P<0.05) were noted in whole grain diets except T3, which had similar figures to that of control. Whole grains produced a larger gizzards (P<0.01). Economic analysis favoured cracked maize and whole bajra treatments, each generating a net profit of NRs. 12.3/bird and NRs. 6.48/bird respectively. This study clearly demonstrated that these whole grains could be successfully fed to broilers in a method of diluting a starter diet. But more research is needed with higher nutrient density starter diets with some adjustments in whole grain dilution to develop an efficient method of whole grain feeding that gives at least equal weights, better FCR, and lower feed costs. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 21-28 DOI: http://dx.doi.org/10.3126/njst.v13i2.7709